2022
DOI: 10.1002/smll.202203125
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Bimetallic‐Based Spinels as Electrocatalysts for the Oxygen Evolution Reaction

Abstract: Among other energy alternatives, such as wind and solar, hydrogen in itself is considered a viable and ideal option due to its zero CO 2 emission, high gravimetric energy density, pollution-free advantages, and independence of weather conditions. [2] However, the traditional production of hydrogen, through steam methane reforming and coal gasification, is by no means feasible in the long term due to its associate carbon footprint. To circumvent the "pitfalls" associated with traditional hydrogen production tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 218 publications
0
39
0
Order By: Relevance
“…The Gibbs free energy variation of the above four-electron transfer process can be calculated using the following eqn (5)–(8). 20,21 Δ G 1 = G MOH − G M − ( G OH − − G e − )Δ G 2 = G MO + G H 2 O(l) − G MOH − ( G OH − − G e − )Δ G 3 = G MOOH − G MO − ( G OH − − G e − )Δ G 4 = G M + G O 2 (g) + G H 2 O(l) − G MOOH − ( G OH − − G e − )…”
Section: The Oer Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gibbs free energy variation of the above four-electron transfer process can be calculated using the following eqn (5)–(8). 20,21 Δ G 1 = G MOH − G M − ( G OH − − G e − )Δ G 2 = G MO + G H 2 O(l) − G MOH − ( G OH − − G e − )Δ G 3 = G MOOH − G MO − ( G OH − − G e − )Δ G 4 = G M + G O 2 (g) + G H 2 O(l) − G MOOH − ( G OH − − G e − )…”
Section: The Oer Mechanismmentioning
confidence: 99%
“…The Gibbs free energy variation of the above four-electron transfer process can be calculated using the following eqn (5)- (8). 20,21…”
Section: The Oer Mechanismmentioning
confidence: 99%
“…Additionally, the amount of oxygen molecules upon electrolyze water process is positively correlated with the amount of •OH, generally the more oxygen molecules produce, the more •OH will be generated. [ 35 , 36 , 37 ] The oxygen evolution activity of CO and MCO electrodes is compared (Figure 2c ). The over‐potential of the MCO electrode at 10 mA cm 2 is about 598 mV, considerably smaller than the CO electrode (798 mV), confirming its superior oxygen evolution activity.…”
Section: Resultsmentioning
confidence: 99%
“…As the consumption of conventional fossil fuels increases dramatically, the search for green, efficient, and renewable energies has become a vital issue for the sustainable development of human society. Meanwhile, with the growing demand for wearable electronics, it is also increasingly essential to explore flexible energy storage devices that are flexible, lightweight, safe, high energy storage, long-life, and mechanically stable. , Metal-air batteries, especially zinc-air batteries (ZABs), are considered ideal energy storage systems for electric vehicles, grid energy storage, wearable portable devices, and other areas by virtue of their high theoretical energy density, reliable safety, low cost, and environmental friendliness. Previous studies have demonstrated that electrochemical oxygen evolution reaction (OER) plays a crucial role in metal-air batteries and other sustainable energy conversion and storage devices. , Because of the multi-step proton-coupled electron transfer involved, however, the inherently slow kinetics of OER has gravely hindered the development of related technologies. , At present, noble metal-based catalysts, for instance, IrO 2 and RuO 2 , have been demonstrated to effectively promote OER but are still severely plagued by element scarcity, expensive cost, and unsatisfactory stability. , In addition, the polymer binder (Nafion) used for the powder catalysts in ZAB assembly often blocks the active site of nanostructured electrocatalysts and raises interface resistance, which also sets obstacles for high OER catalytic performance. , The preparation of self-supporting catalysts not only facilitates the exposure of active sites and reduces resistance but also enhances the binding force with the substrate to resist severe bubble impact that can occur during the OER process. Consequently, it is of great value to develop cost-effective and additive-free OER catalysts with high efficiency and superior durability for the practical application and popularization of ZABs.…”
Section: Introductionmentioning
confidence: 99%